Analysis of reverse logistics results in the sugar-alcohol sector: a case study at a plant in the state of Alagoas, Brazil/ Análise dos resultados da logística reversa no setor sucroalcooleiro: um estudo de caso em uma usina do estado de Alagoas, Brasil - Luana Natali dos Santos Lins; Sara Christina Lima Loureiro; Diego da Guia Santos (Universidade Estadual de Alagoas, 2020)
Reverse logistics is a theme that has been standing out over the years when it comes to operational practices and environmental responsibility. Thus, the present study aims to analyze the results of reverse logistics practice performed by the sugar-alcohol sector in the state of Alagoas through the operations of a plant. For that, a case study was carried out in a state-owned plant, where, through an interview with managers and document analysis, it was possible to identify the importance of such actions to the company's operations. As a result, the mill analyzed has been highlighted with the reuse of sugarcane bagasse for the production of energy, filter cake and vinasse, making this a competitive differential compared to its competitors. It was also observed that such practices aid in the management process as they optimize the productive system and impact on the reduction of costs.